2023
DOI: 10.1093/biolre/ioad009
|View full text |Cite
|
Sign up to set email alerts
|

Anex vivoovulation system enables the discovery of novel ovulatory pathways and nonhormonal contraceptive candidates

Abstract: Ovulation is an integral part of the women’s menstrual cycle and fertility. Understanding the mechanisms of ovulation has broad implications for the treatment of anovulatory diseases and development of novel contraceptives. Now, few studies have developed effective models that both faithfully recapitulate the hallmarks of ovulation and possess scalability. We established a 3D encapsulated in vitro follicle growth (eIVFG) system that recapitulates folliculogenesis and produces follicles that undergo ovulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 79 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…These genes have been implicated in inflammation during ovulation (96). Using the same eIVFG system, our published RNA-seq data also discovered a significant up-regulation of Nts and Tnfrsf9 by 4- and 195-fold, respectively, during ex vivo ovulation (45). These results suggest that excessive FSH promotes the expression of proinflammatory genes; despite that the induction of these transcripts is not sufficient to trigger ovulation, they may cause ovarian inflammation.…”
Section: Discussionmentioning
confidence: 70%
“…These genes have been implicated in inflammation during ovulation (96). Using the same eIVFG system, our published RNA-seq data also discovered a significant up-regulation of Nts and Tnfrsf9 by 4- and 195-fold, respectively, during ex vivo ovulation (45). These results suggest that excessive FSH promotes the expression of proinflammatory genes; despite that the induction of these transcripts is not sufficient to trigger ovulation, they may cause ovarian inflammation.…”
Section: Discussionmentioning
confidence: 70%
“…This procedure enabled us to obtain 150 follicles from 3-5 prepubertal mice. Isolated follicles were encapsulated for in vitro culture as we previously described [77][78][79][80][81]. Briefly, follicles were encapsulated in 0.5% (w/v) alginate hydrogel (Sigma-Aldrich, St. Louis, MO).…”
Section: In Vitro 3d Encapsulated Follicle Growth (Eivfg) Ovulation A...mentioning
confidence: 99%
“…LH binds to its surface receptor in mural granulosa cells and theca cells of a preovulatory follicle, and activates a series of signaling molecules to drive key ovulatory events, including follicle rupture, cumulus cell expansion, and resumption of oocyte meiosis I. We have recently demonstrated that the eIVFG-based ex vivo ovulation not only morphologically recapitulates these key ovulatory events but also conserves the ovulatory gene regulatory pathways, such as those related to epidermal growth factor receptor (EGFR), extracellular signal-regulated kinase 1/2 (ERK1/2), progesterone receptor (PGR), inflammation, and proteolysis [3]. Herein, we further determine whether vitrification of immature follicles preserves the ovulation potential at molecular levels when follicles mature to the preovulatory stage in eIVFG.…”
mentioning
confidence: 99%
“…With fresh follicles as the control, vitrified follicles were warmed and cultured for 8 days in eIVFG [5, 6]. Vitrified and fresh follicles were grown to preovulatory stage and were freed from alginate encapsulation and treated with 1.5 IU/mL human chorionic gonadotropin (hCG) to induce ovulation ex vivo [3]. Follicles were collected at 0, 1, 4, and 8-h post-hCG for single-follicle ribonucleic acid sequencing (RNA-seq, GEO number: GSE227091) using an optimized SMART-seq2 protocol [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation